Decadal analysis of stratospheric ozone depletion using data assimilation and Odin/SMR measurements - Sagi, Kazutoshi (2016)
Serious ozone depletion has been measured every Antarctic spring since the early 80’s. This ozone depletion is considered to be a result of photo-chemical reactions and catalytic cycles resulting from anthropogenic halogen containing gases. facilitated by the formation of Polar Stratospheric Clouds (PSCs). The reactive halogen species are released through heterogeneous reactions on the surface of the particles. Currently, global ozone is recovering during past decades as a result of the Montreal Protocol (1987) on the control of ozone depleting substances (ODSs).Arctic ozone depletion is, on the other hand, less severe and show larger variability than Antarctic loss because of the unstable and warmer condition. However, the Arctic stratosphere has been becoming colder and the Arctic ozone loss in the 2011 winter was comparable to Antarctic losses. Ozone depletion is directly/indirectly linked to the climate because the absorption of UV radiation changes the temperature field. It is therefore important to quantify the loss for future climate prediction.The aim of this thesis is to quantify ozone depletions in several Arctic and Antarctic winters using ozone profiles measured by Odin/SMR and a data assimilation tech- nique which is generally used in numerical weather prediction. The DIAMOND (Dynamical Isentropic Assimilation Model for Odin Data) is used in this thesis. A new vertical transport scheme was implemented into the DIAMOND model to account for the diabatic descent inside the polar vortex during the polar night. The new version of the DIAMOND model was examined for the specific northern winter (2009/2010) when SMILES (Superconducting Submillimeter-Wave Limb-Emission Sounder) ob- served stratospheric species as well as SMR. A decadal record of ozone depletion has been determined by comparing the assimilated fields to passively transported fields initialized by assimilation of SMR ozone data. Ozone retrieved from the emission line at 544GHz has been demonstrated for use in ozone depletion studies in the ...